Hubungan Pengetahuan Dan Sikap Terhadap Obat Tradisional Dan Obat Modern Dengan Tindakan Pemilihan Obat Untuk Swamedikasi Di Kalangan Masyarakat Kecamatan Gondang Kabupaten Sragen - Sekar Meyna Ayuningtyas; Adhi Wardhana Amrullah; Hanugrah Ardya (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Self-medication or self-medication is a treatment carried out by people who suffer from minor ailments that do not have to go to the doctor and do not have to buy drugs with a doctor's prescription. This study aims to analyze the relationship between knowledge and attitude in the selection of drugs for self-medication in the Gondang community, Sragen. The sample of this study consisted of people from Gondang District aged 18–75 years. Data analysis used the Chi-square test. The participation rate of respondents was 95%, namely 381 respondents. 48.56% of respondents had a moderate level of knowledge, 80.05% had a positive attitude towards the use of traditional medicines, and 70.34% of respondents had the act of choosing traditional medicines for self-medication. Theresults of the evaluation test using chi-square obtained a p value value of 0.001 < 0.05 which means that there is a significant relationship with knowledge of traditional medicine selection actions. As for the results of evaluation tests using chi-square knowledge of modern drug selection actions, p values of 0.027 < 0.05 were obtained, which means there is a significant relationship. The results of the evaluation test using chi-square attitude towards traditional medicine selection actions obtained pvalues of 0.546 > 0.05 which means there is no significant relationship. While the results of evaluation tests using chi-square attitudes towards modern drug selection actions obtained p value values of 0.345 > 0.05 which means there is no significant relationship.